Prosedur Pendokumentasian Gaji Karyawan dan Pemindahan Data Karyawan pada PT PLN Nusantara Power Services - Charles Fernando Marpaung; R. Yuniardi Rusdianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study analyzes the procedures for employee payroll documentation and data transfer at PT PLN Nusantara Power Services to enhance the efficiency and accuracy of human resource (HR) administration. Using a descriptive qualitative method, data were collected through library and field research. The findings indicate that digitalizing HR administration improves operational efficiency, transparency, and compliance with regulations. Digital transformation also minimizes errors and supports data risk management. The author's internship experience highlights the importance of responsibility and accuracy in data management to meet professional standards. This research contributes to the development of technology-based administrative systems in the energy sector.